Follow-up study of the composite skill performance during the special preparation period for advanced football players - Abdul Ridha, W. H.; Abbood M. A. Z. (Proximus Journal of Sports Science and Physical Education, 2024)
The objective of the study was to analyze the variations in the performance of complex skills among advanced Dijlah Sports Club football players during the special preparation period. This was done by conducting three repeated measurements with time intervals. The study also included the comparison of human field performance with advanced Dijlah Sports Club football players. The research period spanned from October 5, 2023, to July 22, 2023. The researchers employed a descriptive approach with repeated measurements to conduct their study. The research sample consisted of 20 players. The researchers administered complex skill performance tests and analyzed the data using the SPSS system. The findings indicated that the approach implemented by the trainer was suitable for the research sample. Furthermore, the results demonstrated a significant improvement in the compound skills of the participants, particularly in the third test. The researchers advised coaches to prioritize interdisciplinary testing due to their influence on assessing the effectiveness and appropriateness of the method employed for the players.